Participation Performance of Students’ Basic Teaching Skills in Microteaching - Tutiariani Nasution; Fitri Meliani; Ridwin Purba; Nanda Saputra; Herman Herman (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to describe the participation performance of students' basic teaching skills in microteaching. This quantitative study utilized questionnaire to collect the data. The data is processed based on a standardized scale in the assessment of basic teaching skills using the Likert scale. Based on the distribution of 32 respondents viewed from 7 indicators of opening skills, namely indicators of attracting attention and generating motivation, 23 respondents received a scale of 5 (very good) with an achievement of 0.68. The skills to close the lesson are indicators providing references, showing links, and making summaries. The visible scale is 2 (less) with 27 respondents, and the level of achievement is 0.84. In general, the skills of opening lessons are in a good category, but the skills of closing lessons are still lacking. Observation of the skill to explain, it appears that the achievement score indicators of motivation and clarity (use of language, intonation) got a score of 5 (very good) from 25 respondents, with an achievement of 0.78. In detail, the weaknesses can be seen in the organization of insufficient material explanations, providing relevant examples, and applying fun learning methods. Questions or feedback are only memory and memorization, as seen in 27 respondents who got a scale of 2 (less) with an achievement of 0.87. It means that microteaching provides positive effect in helping them become more confident, gain experience, teach a lesson effectively, communicate effectively, wrap up a lesson, manage a classroom, plan ahead, and manage their time effectively.